النظام القانوني للمجلس الدستوري - بوعمرة, ابراهيم; حفظ الله, عبد العالي (University of Eloued جامعة الوادي, 2020)
تختلف الطبيعة القانونية و المهام المسندة للمجلس الدستوري من بلد لآخر، و في الجزائر فإن المجلس الدستوري يتميز بكثير من الخصوصيات التي تميزه عن غيره، و بالرغم من شدة الأزمات السياسية التي مرت بها البلاد، إلا أن المجلس الدستوري استطاع أن يؤدي دور المؤسسة القوية التي حافظت على استمرارية الدولة بمقوماتها التي بنيت عليها. تتعرض هذه الورقة البحثية بالدراسة للطبيعة القانونية و المهام المسندة للمجلس الدستوري الجزائري، كما تتعرض بالتحليل لصلاحياته و إجراءات عمل المجلس الدستوري و حجية قرارته و آرائه. كما تقدم مجموعة من النتائج و المقترحات التي من شأنها أن تعطي قيمة مضافة في أهمية و موضوعية و حكمة هذه المؤسسة المحورية في البلاد. The legal nature and tasks assigned to the Constitutional Council differ from one country to another, and in Algeria, the Constitutional Council is distinguished by many peculiarities that distinguish it from others, and despite the severity of the political crises that the country has gone through, the Constitutional Council has been able to play the role of a strong institution that has preserved On the continuity of the state with its foundations. This research paper examines the legal nature and tasks assigned to the Algerian Constitutional Council, as well as an analysis of its powers, working procedures, and the authenticity of its decisions and opinions. It also provides a set of results and proposals that would provide some results and proposals that would give added value in the importance, objectivity and wisdom of this pivotal institution in Algeria.
مجلد 11، عدد3
Keywords: المجلس الدستوري ; إجراءات عمل المجلس الدستوري ; إختصاصات المجلس الدستوري ; قرارات المجلس الدستوري ; آراء المجلس الدستوري; Constitutional Council ; Working procedures of the Constitutional Council ; terms of reference for the Constitutional Council ; Decisions of the Constitutional Council ; Views of the Constitutional Council